A reflection of increased financing Equity on returns commons stocks - محمد اياد طاهر; حنتوش مصطفى اكرم (Journal of Economics and Administrative Sciences, 2017)
The research aims to study the effect of an increase in funding the Equity by issuing new common shares on revenues ordinary shares, despite the issuance and marketing costs and the introduction of new shareholders that companies incur when issuing new common shares but it is the most important methods used to finance the Equity is funding the common shares it provides money sufficient to finance the large investments of the company and enhance the confidence of dealers with the company, so I designed this research in order to identify the impact of increased funding Equity issue new common shares to common shares revenues. This research has included some of the theoretical concepts to each of the Equity financing common shares and returns common shares and adopted a search on the Iraqi Central Bank which committed listed on the Iraq Stock Exchange corporate decision (the banking sector) to increase funding for the Equity common shares to 250 million Iraqi dinars at a the lowest, so the population comprised shareholding companies listed on the Iraq Stock Exchange (the banking sector), while the sample has been selected in intentional represented by four companies from the companies that completed respond to the decision of the Iraqi Central Bank requirements to increase funding for the Equity common shares to 250 million Iraqi dinars at a minimum, and has extended the period of research during the period 2014-2009, and used a set of indicators and financial methods to measure the Mngert research and has also been relying on Mjuah of statistical methods in the relationship between the variables and test hypotheses, in order to verify proof of hypotheses have been used simple linear regression as well as the use of interpretation coefficient (identification) for the purpose of measuring Maevsrh independent variable proportion of the changes influenced by the now variable search . The research findings indicated the existence of a significant effect of the increase in Equity financing by issuing new common shares in the revenue ordinary shares.